Effects of gamma irradiation on shelf life and quality of Black Bengal goat meat (Asian-Australasian Journal of Food Safety and Security, 2017)
This study was undertaken to assess the effects of gamma irradiation (0, 1.5, 2, 4 kGy) on shelf life and meat quality of Black Bengal goat. About 3 kg of fresh Black Bengal goat meat samples were taken and divided into four groups like T1 (non-irradiated, control), T2 (irradiated, 1.5 KGy), T3 (irradiated, 2.0 KGy) and T4 (irradiated, 4.0 KGy). Irradiated and non-irradiated meat samples were stored at refrigeration temperature to elucidate the storage effect. One way ANOVA was performed to investigate the effects of gamma irradiation on different groups. Significant differences were found in color and overall acceptability compared to non-irradiated group and only overall acceptability significantly decreased with increasing storage. No significant differences were observed in flavor, tenderness and juiciness between non-irradiated and irradiated groups. Irradiation influenced color and overall acceptability of chevon. Dry matter content was found higher in 4 KGy irradiated group and increased gradually in day intervals. Cooking loss, free fatty acid, peroxide value and thiobarbituric acid-reactive substances indicated 1.5 KGy irradiation rated best. Microbial findings revealed that 2 KGy irradiated group is better due to safe level of microbial loads which increase shelf life of Black Bengal goat meat. Finally, it may be concluded that 1.5 and 2 KGy doses gamma irradiation in Bengal goat meat enhances sensory attributes, physico-chemical and microbial levels found satisfactory.Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 65-73